2017
DOI: 10.1108/jcm-07-2016-1872
|View full text |Cite
|
Sign up to set email alerts
|

Underdog effects: the role of consumption domain and retail crowding

Abstract: Purpose When communicating with consumers, firms frequently highlight their underdog status to evoke a favorable attitude. Previous research has confirmed consumer preference for underdogs over top dogs in various domains. However, very little research has been conducted on the business types and decision contexts in which underdog effects produce the most impact. This paper aims to investigate some of the unexplored boundary conditions of underdog effects and addresses two issues: consumption domain and retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 32 publications
1
27
0
2
Order By: Relevance
“…Most research on underdog-style brand stories have embraced self-consistency theory to explain their superior effectiveness in terms of the fact that most people at some point in their lives have considered themselves as underdogs (Li and Zhao, 2018; Kim et al , 2019; Tezer et al , 2019). As a result of their own underdog disposition, consumers develop a stronger sense of identity with brands that are weaker but determined to improve (Shirai, 2017). To a minor extent, the effectiveness of underdog-style brand stories has also been explained in terms of other contextual drivers, such as the type of consumption domain (hedonic vs utilitarian: Shirai, 2017; Li and Zhao, 2018), the retail environment (crowded vs uncrowded: Li and Zhao, 2018) and the individual’s psychological distance from the brand (Kao, 2019).…”
Section: Underdog Vs Topdog Brand Storytelling Stylesmentioning
confidence: 99%
“…Most research on underdog-style brand stories have embraced self-consistency theory to explain their superior effectiveness in terms of the fact that most people at some point in their lives have considered themselves as underdogs (Li and Zhao, 2018; Kim et al , 2019; Tezer et al , 2019). As a result of their own underdog disposition, consumers develop a stronger sense of identity with brands that are weaker but determined to improve (Shirai, 2017). To a minor extent, the effectiveness of underdog-style brand stories has also been explained in terms of other contextual drivers, such as the type of consumption domain (hedonic vs utilitarian: Shirai, 2017; Li and Zhao, 2018), the retail environment (crowded vs uncrowded: Li and Zhao, 2018) and the individual’s psychological distance from the brand (Kao, 2019).…”
Section: Underdog Vs Topdog Brand Storytelling Stylesmentioning
confidence: 99%
“…Furthermore, Jun et al (2015) argued that the personality trait of empathy influences the underdog effect on brand attitude and thus purchase intentions. Overall, these studies and others on underdog effects have clearly established a positive relationship between underdog brand positioning and consumer’s purchase intentions (Shirai, 2017; McGinnis et al , 2017; Kao, 2015; Jun et al , 2015; Paharia et al , 2010). The topic of underdog effect has, however, received little attention in brand positioning despite its high prevalence.…”
Section: Introductionmentioning
confidence: 52%
“…This positive attitude also influences consumer choices as the perceived value and preference of those brands increase (Salehzadeh and Pool, 2017; Moriuchi and Jackson, 2017; De Cannière et al , 2009; Sheth et al , 1991). Recent research has shown that brand positioning emphasizing the disadvantageous, less privileged condition of a brand (underdog) has been used in practice and has continuously gained research interest (Shirai, 2017; Kao, 2015; Jun et al , 2015; Paharia et al , 2010, 2014). The underdog brand biography by Paharia et al (2010) is one of the most commonly employed in business.…”
Section: Introductionmentioning
confidence: 99%
“…Social stimuli involve the number, type, and behavior of people that appear within the store, including other buyers and salespeople (Robert, 2001), including crowded behavior, employee attitudes, and social interaction between consumers and salespeople that can stimulate impulse buying (Turley & Milliman, 2000). Among these social stimuli, perceived crowding was found the most influential factor of impulse purchase (Miyuri, 2017). This means that the presence and interaction of other shoppers within the store can increase the possibility of impulse purchases.…”
Section: External Stimuli and The Impact On Impulse Buyingmentioning
confidence: 99%
“…Year Contribution the individual's needs Agarwal 2015 Proved that personal traits, including demographic such as gender, income can trigger impulse purchase Miyuri 2017 Perceived crowding was found the most influential factor of impulse purchase Tran 2020 Changing context of society opened out various ways of defining the term Source: Collected and summarised by the authors…”
Section: Authormentioning
confidence: 99%